New Paradigms in the Pathogenesis of Otitis Media in Children - Coticchia, James M.; Chen, Michael; Sachdeva, Livjot; Mutchnick, Sean (Frontiers in Pediatrics, 2013)
Acute otitis media (AOM) is a multifactorial disease with a significant socioeconomic impact. The pathogenesis of AOM is attributed to a variety of well-established internal and extrinsic factors. Recent evidence strongly points to bacterial biofilm formation as an important contributor to this disease entity. The nasopharynx is a likely reservoir for infection with subsequent seeding of pathogens to the middle ear via planktonic shedding. Various modalities have been used to directly detect biofilm formation in the middle ear mucosa of children with AOM. Further insights into this disease may lead to new strategies for prevention and treatment.